Features of spin dynamics in HgCrCdSe and HgCrSe crystals in the vicinity of phase transitions - Bekirov, B.E.; Ivanchenko, I.V.; Popenko, N.A. (Физика низких температур, 2018)
The inhomogeneously broadened EPR lines of the solid solutions Hg₁₋x₋yCrxCdySe and Hg₁₋xCrxSe are rep-resented in the form of spin packets and their temperature evolution is analyzed upon the transition of the crystals to ferromagnetic ordering. In this case, the spin packets being introduced into the consideration are identified with allowed transitions of the localized electrons and with the delocalized electrons. It is established that a characteristic feature of the subsystem of delocalized electrons is the anomalous behavior of the g-factor in the vicinity of the transition to the ferromagnetic state. The introduced spin subsystems, which characterize the localized and delocalized electronic states, allow for explainig the differences in scenarios of the transition to magnetic ordering of crystals with different cluster structures. Just significantly lower concentration of clusters in the HgCrSe crystal leads to a slowing down of flip-flop processes that explains the longer relaxation times of spin packets in this diluted magnetic semiconductor in comparison with the relaxation times of spin packets in the HgCrCdSe crystal in the ferromagnetic temperature range.